Assessment of Cranial Sonographic Findings of Hypoxic Ischemic Brain Injury in Perinatal Asphyxia (Journal of Medicine, 2016)
Background: In perinatal asphyxia, hypoxic ischemic brain injury remains most serious condition causing significant mortality and long term morbidity. Early detection of intracranial changes and its consequences will enhance timely intervention and better out come. Cranial sonography can be done to assess the abnormalities of brain in perinatal asphyxia. Objectives: The objective of this study was to evaluate usefulness of cranial sonography in perinatal asphyxia.Methods: This was an observational study conducted from March 2014 to February 2015 at department of radiology and imaging, Enam Medical College and Hospital. Total 100 neonates with perinatal asphyxia were included in this study. Cranial USG was done in all cases and sonographic abnormalities were evaluated.Result: 56 term (>37 weeks of gestation ) and 44preterm (